2010
DOI: 10.1002/tea.20403
|View full text |Cite
|
Sign up to set email alerts
|

A typology of undergraduate students' conceptions of size and scale: Identifying and characterizing conceptual variation

Abstract: The importance of ''size and scale'' in nanoscience and engineering has been recognized by both scientists and science educators. A solid understanding of this concept is key to the learning of nanoscience. Students, however, have been reported to have considerable difficulty grasping this concept; yet little is known regarding their state of understanding. To address this knowledge gap, we conducted a series of studies that were aimed at exploring the different ways students conceive of ''size and scale'' in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 17 publications
3
48
0
5
Order By: Relevance
“…However, the teaching and learning of concepts related to size and scale present major challenges. For example, Swarat et al (2011) identified three major ways students conceive scale: linear (representing direct observation or experience), proportional, and logarithmic. They found that the most difficult of these categories for students to grasp was the logarithmic scale, but the largest problem was connecting different levels of organization or timeframes.…”
Section: Temporal and Spatial Scalesmentioning
confidence: 99%
“…However, the teaching and learning of concepts related to size and scale present major challenges. For example, Swarat et al (2011) identified three major ways students conceive scale: linear (representing direct observation or experience), proportional, and logarithmic. They found that the most difficult of these categories for students to grasp was the logarithmic scale, but the largest problem was connecting different levels of organization or timeframes.…”
Section: Temporal and Spatial Scalesmentioning
confidence: 99%
“…Even those who are able to construct log scales sometimes describe the linear scale representation as the real one and the log scale as a distortion (Swarat et al, 2011). …”
Section: Impact Of Formal Mathematics Instruction On Magnitude Estimamentioning
confidence: 99%
“…The notion of scale is an excellent case in point (Swarat, Light, & Park, 2011;Tretter, Jones, Andre, Negishi, & Minogue, 2006). Consider that, for example, early in life learners establish an intuitive understanding that a tiny grain of sand (w1 mm) and a massive boulder (w1 m) can be related to one another through scale (of 1:10 3 ).…”
Section: Introductionmentioning
confidence: 99%